1983
DOI: 10.1021/jo00174a002
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of deoxyribonucleic acids: a direct study by carbon-13 nuclear magnetic resonance spectroscopy

Abstract: sulfide, diphenyl disulfide, and diphenyl diselenide, respectively, as well as reduction products 6 and 11. Diphenyl telluride is oxidized to diphenyl telluroxide with 7, but diphenyl selenide is unreactive toward 7. The pertellurane dibromides and dichlorides do not react with olefins in CH2C12 after 48 h in the dark at ambient temperature, although irradiation leads to small amounts of allylic halides. Compounds 9 and 10 are reduced with hydrazine to give ll18 and 1219 in 71% and 89% yields, Br Cl M 12 respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 8 publications
4
30
0
Order By: Relevance
“…18 Careful examination of spectral data (NMR, MS) of thymine and uracil showed that they are similar to the data reported for 9 and 10, isolated by Mishra et al 19 (9) from the sponge Suberites vestigium and Parameswaran et al 20 (9 and 10) from the sponge Tedania anhelans.…”
Section: Resultssupporting
confidence: 74%
“…18 Careful examination of spectral data (NMR, MS) of thymine and uracil showed that they are similar to the data reported for 9 and 10, isolated by Mishra et al 19 (9) from the sponge Suberites vestigium and Parameswaran et al 20 (9 and 10) from the sponge Tedania anhelans.…”
Section: Resultssupporting
confidence: 74%
“…Of the other nitrogens on dA, only reaction at N1 would produce a product with the observed chemical behavior due to its ability to isomerize to an N6-alkylamino derivative (Scheme 5). 7,30,31 Although reaction at N1-dA is unexpected based upon inspection of molecular models, this nitrogen is more nucleophilic than the N7-dA 28. Reaction at N1-dA requires that the Watson–Crick duplex undergo local melting.…”
Section: Resultsmentioning
confidence: 99%
“…We also wanted to ascertain whether the uncharged lesions m1G and m3T, which are structurally analogous with respect to the alkylated position of m1A and m3C, would also be substrates for AlkB. The m1A, m3C, and e3C lesions in the present study are preferentially formed by alkylating agents in single-stranded DNA and have been detected in vitro (5,6,(12)(13)(14)(15)(16)(17)(18) and in vivo (12,17,(19)(20)(21)(22)(23)(24). Although less prevalent, m1G lesions have also been found in vitro (16) and in vivo (19), and m3T in vitro (12,13,16,18,25) and in vivo (12,25).…”
mentioning
confidence: 85%